Relationships Among Atmospheric Suspended Particulates with Different Sizes: A Case Study of Chongqing City - Yan Gui; Haiyang Wang (Atmosphere)
The current study predicts that there would be scaling relationships among atmospheric suspended particulate materials (PMs) with different diameters. Through sampling the particulate materials concentration over different types of land use in municipal areas in Chongqing, analyzing the respective data of the independent concentrations of particulate materials varying in sizes, and testing the predictions, it is found that: (1) there are generally a negative relationships between falling dust of large particulate size (diameter > 10 μm) and floating dust of small ones (diameter ≤ 10 μm); (2) there are positive correlations among the fine particulate materials varying in sizes of iPM10, iPM2.5, and iPM1; (3) there is a disproportionately increase between the particulate materials varying in sizes compared to the respective control; (4) there is a declining-and-rising tendency between the particulate materials reduction rate and the increase in particulate materials along a particulate-size-decline gradient. The results of this study may contribute to understanding the law of the interactions of particulate materials with different particle sizes in the atmosphere and lay a theoretical foundation for the elimination of the atmospheric suspended pollutants.